Pengaruh slogan Pendidikan “Embrace Your Passion, Prepare Your Future” terhadap kreativitas Pelajar SMAK PENABUR Summarecon Bekasi - Limarandani, Alina; Novie Indriani, Maria Dwi; Anastasia Tety Kusuma Astuti; Tuty Mutiah (Jurnal Pewarta Indonesia, 2025)
This study aims to analyze the impact of the educational slogan "Embrace Your Passion, Prepare Your Future" on student creativity at SMAK PENABUR Summarecon Bekasi. This slogan is implemented as part of the school's philosophy, encouraging students to recognize and develop their passions while preparing for a future full of innovation. The research employs Structural Equation Modeling (SEM) using Smart PLS 3.0 software. The results show that the educational slogan has a positive and significant effect on student creativity, with a P-value smaller than 0.05 and T-statistics exceeding the significant threshold. The study also finds that a supportive educational environment plays a crucial role in fostering students' creativity. Therefore, this research recommends that schools create a balance between academic achievement and creativity development by implementing programs that encourage interest exploration and innovation, both inside and outside the classroom. These findings highlight the importance of applying educational slogans as a tool to motivate students in reaching their creative potential, which is highly relevant to the dynamic and competitive demands of the modern workforce.